Indian banking/ edited by C.R. Kothari - Kothari, C.R. (ed.) (Jaipur, 1991)
The present book is the collection of papers from eminent academicians and experienced practitioners wherein various challenges in the realm of social banking and profitability have been highlighted. The volume presents an in depth analysis concerning various issues along with some concrete suggestions for improving the qualitative parameters. Apart from all this, it provides several new thrust areas for further exploration and research. Accordingly, it will prove of immense value not only to the academic community but will be equally rather more useful for planners and policy-decision makers.
Keywords: Economic